2017
DOI: 10.18632/oncotarget.17830
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of leucocyte subpopulations in diffuse large B-cell lymphoma

Abstract: BackgroundRecent studies have suggested that variables related to host adaptive immunity and the tumor microenvironment may predict the outcome in patients with non-Hodgkin's lymphoma. This study was undertaken to determine the prognostic value of peripheral blood leucocyte subpopulations in diffuse large-B-cell lymphoma patients.MethodsWe prospectively analyzed the 16 leukocyte subpopulations using Cytodiff flow cytometric technique in a cohort of 45 diffuse large-B-cell lymphoma patients at a single institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Previous studies indicated circulating CD16 + monocytes predicted prognosis in solid tumors 7 . Our team also found for the first time that the lower CD16− monocytes/CD16 + monocytes ratio was related to worse survival in DLBCL without known mechanisms 5 . In this study, we explored the clinical value of monocyte subsets in T-NHL and the potential mechanisms.…”
Section: -/Cd16 + Monocytes Predict the Prognosis Of T Cell Lympsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies indicated circulating CD16 + monocytes predicted prognosis in solid tumors 7 . Our team also found for the first time that the lower CD16− monocytes/CD16 + monocytes ratio was related to worse survival in DLBCL without known mechanisms 5 . In this study, we explored the clinical value of monocyte subsets in T-NHL and the potential mechanisms.…”
Section: -/Cd16 + Monocytes Predict the Prognosis Of T Cell Lympsupporting
confidence: 52%
“…Tumor microenvironment especially the tumor-associated macrophage (TAM) has been recognized as a promising predictive marker in lymphoma 4 and peripheral blood monocytes are considered the major sources of TAMs. In a recent study we found for the first time that the lower CD16− monocytes/CD16− monocytes ratio seemed to indicate the worse prognosis of diffuse large B cell lymphoma (DLBCL) 5 . Therefore, we prostitute CD16−/CD16 + monocytes may reflect tumor microenvironment and may also be used to predict the survival of T-NHL.…”
mentioning
confidence: 95%
“…Shi et al reported that diffuse large B cell lymphoma (DLBCL) patients with high CD8‐positive T cells and tumoural PD‐L1 expression showed better survival, irrespective of rituximab treatment . However, other researchers reported that an increase in CD8‐positive or TIA1‐positive cytotoxic T cells was associated with poor prognosis in DLBCL patients . In the current study, CD8‐positive T cells showed no definitive role in the better prognosis of ATLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In AML, defective NK cells at diagnosis are associated with increased risk of relapse and transcriptional analysis shows differential expression of TGF-β signaling pathways between highly functional NK cells and dysfunctional NK cells from patients with leukemia [ 3 ]. Decreased number and function of NK cells in the TME of lymphoma predicts a poor prognosis [ 203 ]. Similar to other solid tumors, TGF-β is expressed at high levels by both lymphoma cells and regulatory T cells within the lymphoma tumor microenvironment which is likely one of the immune escape mechanisms employed by lymphomas [ 204 , 205 ].…”
Section: Barriers To Nk Cell Success and Solutionsmentioning
confidence: 99%